Комплекс вправ для формування англійськомовної дискусійної компетенції - Янісів, Михайло; Ділай, Маріанна; Іщук, Мирослава (Видавництво Львівської політехніки, 2017)
This paper presents activities aimed at developing students’ communicative competence in English, in particular their ability to discuss ethical and moral issues. The model of argumentative discussion is described based on the short story The Trimmed Lamp by O’Henry. Useful phrases for specific stages of discussion are given.
Keywords: комунікативна компетенція; проблемно-пошукові комунікативні задачі; комунікативна активність; логічні операції дискусії